Economic policy impact on competitiveness and efficiency of textile industry in central java - P. Eko Prasetyo; Ketut Sudarma; Adang Syamsudin Sulaha (Universitas Islam Indonesia, 2014)
The purpose of this research was to determine the competitiveness and efficiency as well as assessing the impact of economic policies on the performance of the textile industry in Central Java. The competitiveness methods use a RCA, TSI, and IIT Indexes. The policy impacts use Policy Analysis Matrix and sensitivity analysis. The results show that the textile industry in Central Java had only a comparative advantage, but not competitive one. The lower protection level made the textile industry was vulnerable to both internal and external shocks. In general economic efficiency was still lower, so it had lower effect on the productivity and competitiveness level.